The Double-Edged Sword of Vitamin A: Function and Toxicity - Paulina Grzeszczuk; Magdalena Jabłonowska (Quality in Sport)
Introduction: This article investigates the essential functions and health risks of vitamin A, focusing on its metabolic pathways, dietary origins, daily requirements, the clinical consequences of deficiency and the harmful effects of overdose.